Quality Assessment of a Web-Based E-Learning Platform Using ISO/IEC 25010 and End-User Questionnaire - Dicka Apyan Wijaya; Amelia Anggraini (Journal Innovation in Information and Computer Technology, 2025)
The increasing use of web-based e-learning platforms has significantly influenced the way learning activities are conducted in modern education. However, many platforms still face challenges related to usability, system performance, and reliability, which may affect user satisfaction and learning effectiveness. Therefore, evaluating the quality of e-learning systems is essential to ensure that they meet user expectations and support learning processes effectively. This study aims to assess the quality of a web-based e-learning platform using the ISO/IEC 25010 model combined with an end-user questionnaire approach. A quantitative method was applied, and data were collected from 30 respondents consisting of students and instructors. The evaluation focused on four main quality characteristics: functional suitability, usability, reliability, and performance efficiency. The collected data were analyzed using descriptive statistical methods to determine the overall quality level of the system. The results show that the e-learning platform achieved an overall average score of 4.03, which falls into the “good” category. Functional suitability obtained the highest score, indicating that the system effectively meets user needs. Meanwhile, performance efficiency received the lowest score, suggesting that improvements are needed in system response time and resource optimization. In conclusion, the evaluated e-learning platform demonstrates a satisfactory level of quality in supporting online learning activities. However, further improvements are required, particularly in terms of system performance, to enhance user experience and overall effectiveness.